Policy Life Cycle Analysis of Three Australian State-level Public Policies: Exploring the Political Dimension of Sustainable Development. (January 2021) - Goswami, Kuntal; Gerritsen, Rolf
This article analyses the life cycle of three Australian public policies (Tasmania Together [TT], South Australia's Strategic Plan [SASP, ] and Western Australia's State Sustainability Strategy [WA's SSS]). These policies were formulated at the state level and were structured around sustainable development concepts (the environmental, economic, and social dimensions). This study highlights contexts that led to the making of these public policies, as well as factors that led to their discontinuation. The case studies are based on analysis of parliamentary debates, state governments' budget reports, public agencies' annual reports, government media releases, and stakeholders' feedback. The empirical findings highlight the importance of understanding the political dimension of sustainable development. This fact highlights the need to look beyond the traditional three-dimensional view of sustainability when assessing the success (or lack thereof) of sustainable development policies. Equally important, the analysis indicates that despite these policies' limited success (and even one of these policies not being implemented at all), sustainability policies can have a legacy beyond their life cycle. Hence, the evaluation of these policies is likely to provide insight into the process of policymaking.